Problem-based learning effectiveness on micro-blog and blog for students: a case study. Issue 6 (17th August 2016) - Huang, Shu-Hsien; Huang, Yueh-Min; Wu, Ting-Ting; Chen, Hong-Ren; Chang, Shih-Ming
Abstract : Problem-based learning (PBL) is regarded as an effective learning strategy to enhance cognition not only in traditional learning but also in e-learning. In e-learning settings, blogs and micro-blogs can plausibly provide a platform to conduct PBL. Recently, most studies on blogs and micro-blogs have respectively probed satisfaction and learning effectiveness. However, little effort has been made to explore their effectiveness on learning. Therefore, this study explored an application of a PBL approach on a micro-blog and blog by seventh-grade students taking an information ethics course; in particular, the effect of a micro-blog and blog on student learning with different learning achievement levels. Moreover, results showed that the micro-blog had more effect on PBL for low achievement students compared to the blog. This study suggests that using a micro-blog for PBL is more appropriate for the sake of maximizing learning effectiveness, if generally considering students with different learning achievement levels.